PENINGKATAN KOMPETENSI TENTANG UJI KAPASITAS DUKUNG TANAH DI LAPANGAN UNTUK SISWA SMK NEGERI PRINGSURAT : PENINGKATAN KOMPETENSI TENTANG UJI KAPASITAS DUKUNG TANAH DI LAPANGAN UNTUK SISWA SMK NEGERI PRINGSURAT - Rabinah, Aiun Hayatu; Harprastanti, Primasiwi; Mahbub, Jamal; Goro, Garup Lambang; Risman; Warsiti; Mulyono, Tedjo; Nurhadi, Imam; Himam, Muhamad Khudza Alfi; Imansyah, Salmaa R. N (Politeknik Negeri Semarang, 2026)
One of the challenges faced by students from SMKN Pringsurat in the civil construction implementation survey was related to field soil testing. Generally, SMKN Pringsurat students already have a basic understanding of civil engineering competencies, but still experience difficulties in several areas, particularly field soil testing. Therefore, to improve competency, training was conducted on the application of concrete testing in the field. The training focused on soil bearing capacity testing for SMKN Pringsurat. Based on questionnaire results, after the training, an average of >60% of SMKN Pringsurat students were able to correctly understand and understand the soil testing procedure in the field using the DCP tool, as well as how to analyze the test data. Direct training and intensive mentoring were effective methods, making it easier for students to absorb the material. 70% of students stated that the training was easy to understand.